Efektivitas Buah Pisang Untuk Menurunkan Tekanan Darah Diastolik Pada Wanita Hamil Dengan Hipertensi: The Effectiveness Of Bananas To Lower Diastolic Blood Pressure In Pregnant Women With Hypertension - Kartikasari, Ratih Indah; Lestari, Dwi (Universitas Muhammadiyah Sidoarjo, 2016)
Hypertension in pregnancy is increased blood pressure ≥ 140/90 mmHg. Hypertension is the beginning of a sign of eclampsia in pregnancy. In the initial survey of 10 pregnant women found that 40% had hypertension. The research objective to analyze the effectiveness of bananas to the reduction of blood pressure in pregnant women with hypertension. The study design using pre-experimental design approach to one group pre post test design. Samples were taken at 18 people with simple random sampling technique. Instrument used SOP and observation sheet before and after the action. The results showed nearly all pregnant women decreased diastolic blood pressure by 77.8% given bananas for 7 days with a dose three times a day. The results of analysis by Wilcoxon signed rank test p value = 0.001 (p <0.05), the H1 accepted, meaning that there is the influence of bananas to the decline in diastolic blood pressure in pregnant women with hypertension. Based on the results of this study are expected of hypertensive patients that eating bananas to lower blood pressure.